A genomic-based approach combining in vivo selection in mice to identify a novel virulence gene in Leishmania. - Wen-Wei Zhang; Christopher S Peacock; Greg Matlashewski (Public Library of Science (PLoS), 2008)
Infection with Leishmania results in a broad spectrum of pathologies where L. infantum and L. donovani cause fatal visceral leishmaniasis and L. major causes destructive cutaneous lesions. The identification and characterization of Leishmania virulence genes may define the genetic basis for these different pathologies.Comparison of the recently completed L. major and L. infantum genomes revealed a relatively small number of genes that are absent or present as pseudogenes in L. major and potentially encode proteins in L. infantum. To investigate the potential role of genetic differences between species in visceral infection, seven genes initially classified as absent in L. major but present in L. infantum were cloned from the closely related L. donovani genome and introduced into L. major. The transgenic L. major expressing the L. donovani genes were then introduced into BALB/c mice to select for parasites with increased virulence in the spleen to determine whether any of the L. donovani genes increased visceral infection levels. During the course of these experiments, one of the selected genes (LinJ32_V3.1040 (Li1040)) was reclassified as also present in the L. major genome. Interestingly, only the Li1040 gene significantly increased visceral infection in the L. major transfectants. The Li1040 gene encodes a protein containing a putative component of an endosomal protein sorting complex involved with protein transport.These observations demonstrate that the levels of expression and sequence variations in genes ubiquitously shared between Leishmania species have the potential to significantly influence virulence and tissue tropism.